Practice and Exploration of a Clinical Nursing Student Teaching Model Based on the Combination of Flipped Classroom, MOOCs, and Gibbs’ Reflective Cycle: A Case Study of The First Affiliated Hospital of Anhui Medical University - Wang, Dongmei (Pacific International Journal, 2025)
This study explores the design, implementation, and evaluation of an integrated clinical nursing student teaching model combining flipped classroom pedagogy, Massive Open Online Courses (MOOCs), and Gibbs’ Reflective Cycle at The First Affiliated Hospital of Anhui Medical University. Utilizing a mixed-methods case study approach, the research investigates the model’s effectiveness in enhancing nursing students’ clinical skills, critical thinking, reflective abilities, and overall learning satisfaction. Results indicate significant improvements in practical competencies and reflective practice compared to traditional teaching methods. Students demonstrated higher engagement, autonomy, and deeper professional insight through structured reflection and active learning. Clinical instructors highlighted benefits in facilitating student-centered learning despite initial challenges in digital resource preparation. This integrated model presents a promising approach to bridging theoretical knowledge and clinical practice, supporting the development of competent, reflective nursing professionals. Recommendations for broader implementation and further refinement are discussed to optimize teaching outcomes in clinical nursing education.